JENIS DAN SEBARAN SATWA BURUNG DI HUTAN DESA LATDALAM KECAMATAN TANIMBAR SELATAN KABUPATEN KEPULAUAN TANIMBAR - Dulce Masella; John Sahusilawane; Lesly Latupapua (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the frequency of bird species in the Northern Block, which is part of Indonesia's biodiversity. Based on the available data, Indonesia is home to 1,836 bird species, 558 of which are protected and 542 are endemic. The research also includes a map of the study site showing the observation areas. The results show that the bird species found include Zebra Dove, Tanimbar Corella, Moluccan Coucal, Golden-bellied Flycatcher, Tanimbar Thrush, Great Egret, Brahminy Kite, Red-cheeked Parrot, Java Sparrow, Tanimbar Lorikeet, and Great-billed Parakeet. The distribution of birds in the Latdalam Village Forest is divided into four blocks: the northern block has 8 species, the southern block has 6 species, the eastern block has 7 species, and the western block has 5 species. The outcome of this research is expected to contribute to the understanding and conservation of biodiversity in Indonesia and provide useful information for natural resource management.